Fusobacterium-associated molecular and immunological alterations in colorectal cancer: Insights from a Norwegian cohort - Omran, Thura Akrem; Subirats Camacho, Jose Luis; Senthakumaran, Thulasika; Gundersen, Gro; Alte, Annette Knapskog; Randen, Ulla; Tunsjø, Hege Smith; Sæther, Per Christian; Bemanian, Vahid (Frontiers in Immunology, 2025)
BackgroundThe gut microbiome may significantly influence the development of colorectal cancer (CRC), with Fusobacterium species playing a key role. Recent research has identified Fusobacterium animalis as the predominant Fusobacterium species in CRC tumors. This pilot research explores the immunological and molecular interactions associated with F. animalis and other Fusobacterium species in Norwegian CRC patients.MethodsTumor samples from 25 CRC patients were divided by Fusobacterium load and analyzed for molecular alterations, immunological gene expression, and macrophage polarization. Fusobacterium-high tumors were associated with microsatellite instability (MSI).ResultsAnalysis of differential immune gene expression, combined with correlation analyses, identified 25 genes, including C-X-C motif chemokine ligand 8 (CXCL8), interleukin-6 (IL6), indoleamine 2,3-dioxygenase 1 (IDO1), and secreted phosphoprotein 1 (SPP1), that exhibited significant associations with Fusobacterium abundance in this cohort. Analysis of Fusobacterium adhesion protein 2 (Fap2) revealed active transcription and constitutive expression across multiple colonic sites, including CRC tumor tissues, adjacent non-neoplastic tissues, the ascending colon, and the sigmoid colon. The analysis revealed a positive correlation between RNA levels of Fusobacterium-specific genes (fap2 and nusG) and immune genes (CXCL8, IL6, SPP1, and IDO1) across different colonic sites. This suggests that the abundance of active Fusobacterium cells is related to and possibly influences the pro-inflammatory response in the colonic microenvironment. Although arginase 1 (ARG1) expression was elevated in Fusobacterium-high tumors, no significant link was found between Fusobacterium abundance and M2 macrophage polarization, contradicting previous studies.ConclusionsHigh Fusobacterium, dominated by F. animalis, was linked to increased immune gene expression and constitutive fap2 activity. M2 polarization was unaffected, possibly reflecting in vivo tumor complexity.